2020
DOI: 10.14735/amko2020171
|View full text |Cite
|
Sign up to set email alerts
|

Levels of NT-proBNP and troponin T in cancer patients - mini-review

Abstract: Background: Natriuretic factors are peptidic substances produced by atrial and ventricular myocardium. Primary stimulus to the synthesis of these factors is intramural pressure of atriums by the increase of venous return during intravascular hypervolemia. They may serve as useful cardiac markers in clinical practice. The elevation of N-terminal fragment of atrial natriuretic peptide is characteristic for cardiac failure. Troponin T is a basic component of muscle and is specific for myocardial cell. It is a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although NT-proBNP was originally identified as a cardiac biomarker, its utility is now expanded as a ­cardio-oncology biomarker. 46 …”
Section: Biomarkers Of Cahdmentioning
confidence: 99%
“…Although NT-proBNP was originally identified as a cardiac biomarker, its utility is now expanded as a ­cardio-oncology biomarker. 46 …”
Section: Biomarkers Of Cahdmentioning
confidence: 99%
“…At the same time, echocardiography can intuitively show the anatomical structure and hemodynamic changes of the heart, and detect the systolic and diastolic functions of the heart (7). Many studies have shown that heart-specific biomarkers such as N-terminal pro-B-type natriuretic peptide (NT-proBNP) may be valuable in identifying high-risk patients (8)(9)(10). The etection of NT-proBNP is convenient, quick and cheap.…”
Section: Introductionmentioning
confidence: 99%